Ethylene is the key phytohormone to enhance arsenic resistance in Arabidopsis thaliana - Yiping Zou; Yaping Liu; Wei Li; Qingqing Cao; Xue Wang; Zhubing Hu; Qingsheng Cai; Laiqing Lou (Ecotoxicology and Environmental Safety, 2024)
The toxic metalloid arsenic is prevalent in the environment and poses a threat to nearly all organisms. However, the mechanism by which phytohormones modulate arsenic resistance is not well-understood. Therefore, we analyzed multiple phytohormones based on the results of transcriptome sequencing, content changes, and related mutant growth under arsenic stress. We found that ethylene was the key phytohormone in Arabidopsis thaliana response to arsenic. Further investigation showed the ethylene-overproducing mutant eto1–1 generated less malondialdehyde (MDA), H2O2, and O2•- under arsenic stress compared to wild-type, while the ethylene-insensitive mutant ein2–5 displayed opposite patterns. Compared to wild-type, eto1–1 accumulated a smaller amount of arsenic and a larger amount of non-protein thiols. Additionally, the immediate ethylene precursor, 1-aminocyclopropane-1-carboxylic acid (ACC), enhanced resistance to arsenic in wide-type, but not in mutants with impaired detoxification capability (i.e., cad1–3, pad2–1, abcc1abcc2), which confirmed that ethylene regulated arsenic detoxification by enhancing arsenic chelation. ACC also upregulated the expression of gene(s) involved in arsenic detoxification, among which ABCC2 was directly transcriptionally activated by the ethylene master transcription factor ethylene-insensitive 3 (EIN3). Overall, our study shows that ethylene is the key phytohormone to enhance arsenic resistance by reducing arsenic accumulation and promoting arsenic detoxification at both physiological and molecular levels.